2019
DOI: 10.13057/biodiv/d200528
|View full text |Cite
|
Sign up to set email alerts
|

Niche partitioning on Sumatran Elephant (Elephas maximus sumatranus) and human in space and resources in Riau, Indonesia

Abstract: Abstract. Sukmantoro YW, Alikodra HS, Kartono AP, Efransjah. 2019. Niche partitioning on Sumatran Elephant (Elephas maximus sumatranus) and human in space and resources in Riau, Indonesia. Biodiversitas 20: 1362-1373. Research on elephant and human niches at Balai Raja and Tesso Nilo have been done for 6 years (2012-2017). The study was conducted by recording the distribution of elephants and communities. The distribution of elephants was identified through an installed GPS Collar in 3 groups of elephants (But… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Elephant research in Balai Raja and Tesso Nilo showed results that there was no difference in niches between the wet and dry seasons (Sukmantoro et al 2019b). Research by Sitompul (2011) shows that the season is more influential on elephant feeding behavior, whereas elephant Seblat tended to browse more than graze in the wet season.…”
Section: Sumatran Elephant's Daily Movement Pattern Characteristicsmentioning
confidence: 99%
“…Elephant research in Balai Raja and Tesso Nilo showed results that there was no difference in niches between the wet and dry seasons (Sukmantoro et al 2019b). Research by Sitompul (2011) shows that the season is more influential on elephant feeding behavior, whereas elephant Seblat tended to browse more than graze in the wet season.…”
Section: Sumatran Elephant's Daily Movement Pattern Characteristicsmentioning
confidence: 99%
“…However, knowledge of elephant roaming is essential for humans. The range of humans is undoubtedly higher than elephants globally, and spatial planning is vital to reduce conflicts between humans and elephants (Sukmantoro et al 2019).…”
Section: Behavior and Roaming Area (Home Range) Of The Sumatran Eleph...mentioning
confidence: 99%